2019
DOI: 10.3390/w11071454
|View full text |Cite
|
Sign up to set email alerts
|

Development of Threshold Levels and a Climate-Sensitivity Model of the Hydrological Regime of the High-Altitude Catchment of the Western Himalayas, Pakistan

Abstract: Water shortages in Pakistan are among the most severe in the world, and its water resources are decreasing significantly due to the prevailing hydro-meteorological conditions. We assessed variations in meteorological and hydrological variables using innovative trend analysis (ITA) and traditional trend analysis methods at a practical significance level, which is also of practical interest. We developed threshold levels of hydrological variables and developed a non-parametric climate-sensitivity model of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 63 publications
(133 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, [75] found an increase in the frequency of wet precipitation days from the northeast to the middle parts of the northern highlands of Pakistan. The trends in temperature and precipitation of our previous study i.e., [45] were found consistent with our current study but runoff in the upper part of the KRB was found to increase in comparison to the lower part (downstream) of the basin. Moreover, [3] also identified the lack of a trend in the runoff of the upper and middle stream of the Syr Darya River basin, and their results were found consistent with our current study.…”
Section: Trends In Hydro-climatic Variablessupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, [75] found an increase in the frequency of wet precipitation days from the northeast to the middle parts of the northern highlands of Pakistan. The trends in temperature and precipitation of our previous study i.e., [45] were found consistent with our current study but runoff in the upper part of the KRB was found to increase in comparison to the lower part (downstream) of the basin. Moreover, [3] also identified the lack of a trend in the runoff of the upper and middle stream of the Syr Darya River basin, and their results were found consistent with our current study.…”
Section: Trends In Hydro-climatic Variablessupporting
confidence: 91%
“…Moreover, Khattak [78] observed increasing trends in temperature and runoff but noted an inconsistent pattern for precipitation trend in UIB, Pakistan. Their precipitation and temperature innovative trends were found consistent, whereas runoff innovative trends were found conflicting with the findings of [45].…”
Section: Abrupt Changes In the Hydrological Time Seriesmentioning
confidence: 62%
See 1 more Smart Citation
“…One of the most obvious manifestations of climate change is its influence on water balance and hydrological processes across the globe, and there is notably a heightened awareness of hydrological responses to climate variations [1]. Impacts vary across the globe, with recent climate variations and developments impacting ecological conditions in the Small Aral Sea in Russia [2]; water shortages in Pakistan, which are among the most severe in the world [3] and further impact ecosystem services [4]; and increased droughts in the semi-arid northeastern region of Brazil, which is one of the poorest rural communities in the country [5]. The Tibetan Plateau in Pakistan, referred to as the "Water Tower of Asia", owing to its unique geographical characteristics, plays an important role in the East Asian and global atmospheric circulation patterns, and is experiencing warming with profound impacts on snowmelt and sustainable water resources for major rivers in Asia [6].…”
Section: Introductionmentioning
confidence: 99%
“…Addressing different parts of the water balance, from precipitation [6] and evapotranspiration [9] to runoff [1][2][3]7,8] and impacts to water resources [2][3][4][5]7,8], these papers investigated the performance of hydrological models and GCMs, projected ecological and hydrological changes to basins [1,2,[4][5][6][7][8], and used a suite of analytical and numerical tools to improve both historical calibration/validation capabilities [2,8] and future climate modeling performance [4,5,9].…”
Section: Introductionmentioning
confidence: 99%